Differential Role of Sp100 Isoforms in Interferon-Mediated Repression of Herpes Simplex Virus Type 1 Immediate-Early Protein Expression - Negorev, Dmitri G. (American Society for Microbiology, 2006)
Nuclear domains called ND10 or PML nuclear bodies contain interferon (IFN)-upregulated proteins like PML and Sp100. Paradoxically, herpes simplex virus 1 (HSV-1) begins its transcriptional cascade at aggregates of ND10-associated proteins, which in turn are destroyed by the HSV-1 immediate-early protein ICP0. While PML is essential in the formation of ND10, the function of Sp100 in the cells' defense against viral infection is unknown. In this study we investigated the potential antiviral effect of IFN-β-induced Sp100. We found that IFN-β treatment leads to a differential accumulation of four Sp100 isoforms in different cell lines. Using an HEK293 cell line derivative, 293-S, producing no detectable amounts of Sp100 even after IFN exposure, we analyzed individual Sp100 isoforms for their effect on HSV-1 infection. Sp100 isoforms B, C, and HMG, but not Sp100A, suppressed ICP0 and ICP4 early after infection. Isoforms B, C, and HMG suppressed expression from the ICP0 promoter in transient transfection, whereas Sp100A enhanced expression. Moreover, Sp100A localized in ND10, whereas the repressive isoforms were either dispersed within the nucleus or, at unphysiologically higher expression levels, formed new aggregates. The repressive activity was dependent on an intact SAND domain, since Sp100B bearing a W655Q mutation in the SAND domain lost this repressive activity and accumulated in ND10. Using RNA interference to knock down the repressive Sp100 isoforms B, C, and HMG, we find that they are an essential part of the IFN-β-mediated suppression of ICP0 expression. These data suggest that repression by the Sp100 isoforms B, C, and HMG takes place outside of ND10 and raise the possibility that viral genomes at Sp100A accumulations are more likely to start their transcription program because of a more permissive local environment.